Accumulation Patterns of Metabolites Responsible for the Functional Quality of Virgin Olive Oil during Olive Fruit Ontogeny - Pilar Luaces; Jesús Expósito; Paula Benabal; Mar Pascual; Carlos Sanz; Ana G. Pérez (Antioxidants, 2023)
The health-promoting antioxidant properties of virgin olive oil (VOO) are today considered priority targets in the new olive breeding programs. Given that these properties depend mainly on its phenolic fraction, whose origin lies in the phenolic compounds present in olive fruit, the objective of this study was to provide further insight into the accumulation dynamics of the main antioxidant compounds, including both polar phenolics and lipophilic tocopherols, during the ontogeny of the olive fruit. Data obtained show that, albeit with significant differences, all the studied genotypes share just after fruit set an intense increase in the synthesis of tyrosol and hydroxytyrosol derivatives, by far the main phenolic compounds of the olive fruit, and a subsequent steady decrease along fruit development and ripening. The accumulation dynamics of flavonoids and tocopherols were different from those of tyrosol and hydroxytyrosol derivatives, presenting a peak of synthesis just before the onset of fruit ripening, and then in general, their content decreases throughout the ripening phase. In the case of flavonoids, all genotypes also share a strong increase in the accumulation of anthocyanins in the final stages of fruit ripening, coinciding with the change in fruit color. Furthermore, the results during the fruit ripening process evidenced that the content of tyrosol and hydroxytyrosol derivatives and tocopherols in the fruit largely determines the content of these groups of compounds in the oil. The information acquired could be useful for the selection of the most suitable moment in the ontogeny of the olive fruit for the search for key genes in the biosynthesis of phenolic compounds.